Factors and Their Correlation with Injury Severity of Elderly Pedestrian Traffic Accidents - Tae gyu Hyun; Seok-Ran Yeom; Sung-Wook Park; Deasup Lee; Hyung bin Kim; Il Jae Wang; Byung Gwan Bae; Min keun Song; Youngmo Cho (Journal of Trauma and Injury)
Purpose No previous study has assessed elderly pedestrian traffic accidents based on a nationwide database. This study aimed to help primary physicians who examine patients in emergency departments to determine and make prompt and accurate treatment decisions. Methods This study used data from the Emergency Department-based Injury In-depth Surveillance from 2013 to 2017, managed by the Korea Centers for Disease Control and Prevention. Pedestrians aged ≥65 years were included, and using multivariate logistic regression multiple factors were analyzed to determine their relationship with injury severity. Results Of 227,695 subjects, 6,498 were included, of whom 2,065 (31.8%) were severely injured. There were more female than male patients in all severity groups. Most accidents occurred in the afternoon and on general roads. In the multivariate analysis, the odds ratio (OR) of injury severity for male pedestrians was 1.165 (95% confidence interval: 1.034–1.313, p=0.012). Older age of patients and the use of ambulances were associated with greater injury severity. The accident time affected the degree of injury severity; i.e., compared to dawn, injury severity increased in the morning (OR: 1.246, p=0.047) and decreased at night (OR: 0.678, p<0.001). A significant difference was noted in the correlation between the type of vehicle causing the accident and the accident severity; i.e., motorcycle accidents had lower severity than bicycle accidents (OR: 0.582, p=0.047). Conclusions Injury severity was correlated with sex, age, transportation to the ED, TA onset time, and type of vehicle. The study results suggest that injury severity may be positively reflected in initial assessments and overall integrated treatments by physicians and in the related policies.